Key Differences Between GOLD 2026 and Current Polish Guidelines in the Diagnosis and Treatment of COPD - Franaszek, Jakub; Fahim, Knieszko; Herchi, Nadia; Jabrzyk, Martyna; Patrycja Jarczyńska; Kijowski, Wojciech; Klusek, Mateusz; Michalak, Karolina; Przybył, Maciej (Quality in Sport, 2026)
Chronic obstructive lung disease is recurrently one of the most common causes of morbidity and death in the world, it takes third place among death causes. The dynamic development of medical knowledge provides regular input into recommendations for the diagnosis and treatment of this disease. The goal of this thesis was comparison of most up-to-date GOLD 2026 recommendations with most current recommendations for diagnosis and treatment of COPD in force in Poland and pointing out the differences in both documents. The analysis shows that basic rules of diagnostics and primary treatment are in common and are based on assessment of the symptoms, risk of exacerbations and spirometry results. The differences come from novelty approach to COPD classification according to GOLD 2026 recommendations and availability of new treatments of exacerbations. Areas like disease monitoring, patient education or effectiveness of therapy are very similar and could be easily implemented into Polish clinical practice. The main difference remains the use of new biological therapy in treating COPD. Implementation of those new solutions could be difficult in Polish medical care due to financial reasons. Availability of these drugs is also a important factor.